1980
DOI: 10.1007/bf00443044
|View full text |Cite
|
Sign up to set email alerts
|

A compilation of published reports of mycoses in animals in India

Abstract: The available published reports on animal mycoses in India and the fungal agents isolated from animal material are discussed. Among dermatophytes, the occurrence of Trichophyton verrucosum, T. mentagrophytes, T. rubrum, T. equimum, T. violaceum, T. simii, T. tonsurans, T. terrestre, T. ajelloi, Microsporum canis, M. gypseum and M. namum has been reported. Cases of aspergillosis, candidiasis, phycomycosis, rhinosporidiosis, epizootic lymphangitis, mycotic abortions and mycotic mastitis have been recorded in ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…Trichophyton verrucosum is the most common dermatophyte that affects camels Fadlelmula et al, 1994;Wisal et al, 2010) The results obtained in the present study were in concurrence to the findings of Moore and Jaciow (1979), Monga and Mohapatra (1980), Mukherji et al, (1992), Kuttin et al, (1986) and Almuzaini et al, (2016). Almuzaini et al, (2016) had concluded that ringworm is a common disease affecting young dromedary camels below three years of age and T. verrucosum is a common cause.…”
Section: Resultssupporting
confidence: 90%
“…Trichophyton verrucosum is the most common dermatophyte that affects camels Fadlelmula et al, 1994;Wisal et al, 2010) The results obtained in the present study were in concurrence to the findings of Moore and Jaciow (1979), Monga and Mohapatra (1980), Mukherji et al, (1992), Kuttin et al, (1986) and Almuzaini et al, (2016). Almuzaini et al, (2016) had concluded that ringworm is a common disease affecting young dromedary camels below three years of age and T. verrucosum is a common cause.…”
Section: Resultssupporting
confidence: 90%
“…verrucosum infection can be considered to be a cosmopolitan disease as, over time, it has been reported in livestock and sometimes in people in a number of different countries from all continents [5][6][7][8][9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25]. In Pakistan, several studies have documented the role of this fungal species in human ringworm cases [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually transmitted from soil and can be secondarily transmitted by animals to humans [1]. In animals, dermatophytic lesions due to M. gypseum are most often localized in nails, pinnae, and paws [19]. This species has been cited as the etiologic agent of infection in many domestic and wild animals such as rabbit, horses, camels, pigs, wild ruminants [3], cats, dogs [20] and wild felids (ocelot) [5].…”
Section: Discussionmentioning
confidence: 99%